Large amplitude electromagnetic solitons in a fully relativistic magnetized electron-positron-pair plasma. Issue 9 (1st November 2020) - Banerjee, Gadadhar; Dutta, Sayantan; Misra, A.P.
Highlights: Eelectromagnetic solitary waves can propagate as compressive or rarefactive type solitons. The electromagnetic solitons exist symmetrically for the wave magnetic field. Both the sub-Alfvénic and super-Alfvénic solitons exist in the weakly relativistic regime. Only sub-Alfvénic solitons exist in the ultrarelativistic regime. Abstract: Nonlinear propagation of purely stationary large amplitude electromagnetic (EM) solitary waves in a magnetized electron–positron (EP) plasma is studied using a fully relativistic two-fluid hydrodynamic model which accounts for physical regimes of both weakly relativistic ( P ≪ nmc 2 ) and ultrarelativistic ( P ≫ nmc 2 ) random thermal energies. Here, P is the thermal pressure, n the number density and m the mass of a particle, and c is the speed of light in vacuum. While both the sub-Alfvénic and super-Alfvénic solitons coexist in the weakly relativistic regime, the ultrarelativistic EP plasmas in contrast support only the sub-Alfvénic solitons. Different limits of the Mach numbers and soliton amplitudes are also examined in these two physical regimes.